Tanggung Gugat ( Pertanggungjawaban ) Pemerintah di Indonesia dan Netherland - Firzhal Arzhi Jiwantara; Anies Prima Dewi; Ady Supryadi (CV. Ulil Albab Corp, 2022)
The liability in Indonesia is included as the Government's responsibility, namely as a compulsory compliance obligation of the state or government or government officials or other officials who carry out government functions as a result of an objection, a lawsuit, a judicial review, which is submitted by a person, the community, an entity civil law either through court settlement or out of court. In this case as a form of Government responsibility both in civil and administrative matters. While accountability or accountability of the Government in the Netherlands (civil law system) are known to several teachings regarding civil liability, namely: 1) Accountability based on mistakes (schuldaansprakelijkheid). 2) Liability based on an error with an inverse proof load (schuldaansprakelijkheid met omkering van de bewijslast). 3) Liability based on risk (risicoaansprakelijkheid). In the Dutch legal system the equivalent of strict liability is risk-aansprakelijkheid. Responsibility based on risk is a form of responsibility that is not based on the element of error for the following activities: 1) hazardous material management; 2) waste management installation; and 3) drilling mining activities. The Defendant is free from responsibility based on risk, if: 1) loss arises as a result of war; 2) losses due to extraordinary natural events; 3) losses due to obeying authority orders; 4) losses due to the victim's own actions; 5) losses due to third party actions.